Characterizing the pine wilt disease pathosystem in the Front Range Region of Colorado - Atkins, David, author; Davis, Seth, advisor; Stewart, Jane, advisor; Wall, Diana, committee member; Tinkham, Wade, committee member (Colorado State University. Libraries, 2020)
Pine wilt disease, caused by the pinewood nematode (Bursaphelenchus xylophilus; PWN), is one of the most damaging invasive species in Asia. Tree mortality associated with PWN has recently been reported in Colorado and surrounding states. There remains little documentation on PWN incidence in native pine species or the biology of potential vectors in the Rocky Mountain region. Here we regionally surveyed for PWN in host trees and two putative insect vectors (Monochamus clamator & M. scutellatus) for two years to develop vector flight phenology models and test the hypothesis that disturbance factors predict vector abundance across the landscape. Flight phenology was similar between vectors: flight initiated in mid-July and continued into October for both species. PWN was distributed throughout the Front Range at rates lower than those reported in the putative native range (Host: 3.6%; Vector 4.2%). Infection rate in hosts varied among sites (0-89%), and four 'epicenters' of vector infectivity were identified. We also report the first incidence of PWN-M. clamator association in the U.S. The four identified epicenter sites varied in the timing of anomalous infection frequency, and flight phenology of infective vectors differed between epicenter and peripheral sites. Monochamus populations were found primarily in natural forest areas and seasonally migrate in small numbers to urban areas. Landscape factors such as proximity to burned area were positively correlated with Monochamus abundance. Synthesis and applications: Our study describes PWN infection frequency to be greater than that expected of a newly introduced pathogen, but lesser than the eastern United States and Canada where PWN is known to be established. Our findings provide tools that can predict exposure windows of disease exposure, which were observed to be highest in the early season in Colorado. We also describe the threat that populations of PWN in wildland forests pose to urban landscapes, and how this risk varies seasonally. These findings collectively serve characterize PWN distribution in the native ecosystem and provide tools that can be used by decision-makers and managers to proactively manage the spread of pine wilt disease.
Keywords: pinewood nematode; tree disease; pine wilt disease; entomology; ponderosa pine; Monochamus